Mysticism; the Spirit of Islam - Aliakbar Hashemi (حکمت اسرا, 2017)
In this paper, the relationship between Islamic mysticism and the teachings of Islam, including Quran, traditions and traditional and practical manner are explained. The main question of this article is what is the relationship between mysticism and Islam as fourfold relation? On this basis, it has been tried to show the high rank of mysticism among other Islamic sciences and to remove the charge. The proper way to do this is to study the main teachings of mysticism and compare it with Islamic teachings. Thus, by plotting four discussions, the origins of mysticism, the "Islamic beliefs of the mystical doctrines", "revelation, inspiration, discovery," and "shari'a, tariqa, truth" are answered to the sub-queries derived from the analysis of the main question. This will provide a response to the original question. The result is that the relationship between mysticism and Islam is not general opposition; mysticism has a consistent theme with Islam, and this adjustment is in detail, but also the same. Therefore, mysticism is an absolutely more specific than Islam, and is more closely the same, and there are two equal ratios between them. Mysticism has not missed any part of religion; it focuses on all sections, levels, and layers of religion. On the other hand, in the most complete and excellent form of understanding religion, no part of religion has been left out of the mystical view. Mysticism is the spirit of religion that is present in all its parts and layers.